Biochemistry, mutagenesis, and oligomerization of DsRed, a red fluorescent protein from coral - Baird, Geoffrey S. (The National Academy of Sciences, 2000)
DsRed is a recently cloned 28-kDa fluorescent protein responsible for the red coloration around the oral disk of a coral of the Discosoma genus. DsRed has attracted tremendous interest as a potential expression tracer and fusion partner that would be complementary to the homologous green fluorescent protein from Aequorea, but very little is known of the biochemistry of DsRed. We now show that DsRed has a much higher extinction coefficient and quantum yield than previously reported, plus excellent resistance to pH extremes and photobleaching. In addition, its 583-nm emission maximum can be further shifted to 602 nm by mutation of Lys-83 to Met. However, DsRed has major drawbacks, such as strong oligomerization and slow maturation. Analytical ultracentrifugation proves DsRed to be an obligate tetramer in vitro, and fluorescence resonance energy transfer measurements and yeast two-hybrid assays verify oligomerization in live cells. Also, DsRed takes days to ripen fully from green to red in vitro or in vivo, and mutations such as Lys-83 to Arg prevent the color change. Many potential cell biological applications of DsRed will require suppression of the tetramerization and acceleration of the maturation.